Proposal for an Inland School Ship for the Danube Region - Martin Jurkovic; Andrej David; Csaba Hargitai (Communications - Scientific letters of the University of Zilina, 2016)
Aim of this study is the definition of a framework for the actual realisation of a common school ship in the Danube region. After a brief outline of best practice examples for (inland navigation) school ships in Europe, the study goes on with the summary of the technical aspects of the Danube School Ship and description of the feasible vessel design (with and without lifting wheelhouse) which responds to the previous research analyses.